1989
DOI: 10.1254/jjp.49.225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psychotropic drugs on the contents of melatonin, serotonin and N-acetylserotonin in rat pineal gland.

Abstract: Abstract-In the dark phase, the effects of the psychotropic drugs on the contents of melatonin, serotonin (5-HT) and N-acetylserotonin (NAS) in rat pineal gland were examined. The pineal gland was removed at a certain period of time after subcutaneous injection of the drugs. 5-HT, NAS and melatonin contents in the pineal gland were determined by high performance liquid chromatography with fluorometric detection. A dose-dependent decrease was observed for melatonin content in the administration of diazepam (DZP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…The failure of diazepam given to the intact rat before the onset of darkness to affect the normal nocturnal rise in NAT activity confirms the report of Zatz and Brownstein [1979] but seems at variance with Wakabayashi et al [1989], who reported reduced pineal melatonin content under these conditions without a change in N-acetylserotonin content. This disparity could result from the differences in species (Fischer vs. Wistar), route of drug administration (subcutaneous vs. intraperitoneal), or the effects of the vehicle carrier (ethanolpropylene glycol in this study).…”
Section: Discussionsupporting
confidence: 84%
“…The failure of diazepam given to the intact rat before the onset of darkness to affect the normal nocturnal rise in NAT activity confirms the report of Zatz and Brownstein [1979] but seems at variance with Wakabayashi et al [1989], who reported reduced pineal melatonin content under these conditions without a change in N-acetylserotonin content. This disparity could result from the differences in species (Fischer vs. Wistar), route of drug administration (subcutaneous vs. intraperitoneal), or the effects of the vehicle carrier (ethanolpropylene glycol in this study).…”
Section: Discussionsupporting
confidence: 84%
“…We report herein, that 21 days administration of diazepam decreased pineal melatonin levels and altered pineal NAT activity, without affecting the activity of HIOMT. We show that diazepam administration on a long-term basis resulted in an inhibition of NAT activity and a decrease of pineal melatonin concentrations to the same magnitude as that observed with acute diazepam administration (Wakabayashi et al 1989(Wakabayashi et al , 1991a(Wakabayashi et al , 1991b. Therefore, a chronic treatment with diazepam compared to an acute administration did not affect differently pineal melatonin synthesis, which strongly suggests that diazepam affects pineal melatonin synthesis, at least in the rat, at the beginning of the treatment.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, it has been shown that a single subcutaneous injection of diazepam at a dose of 3 mg/kg body weight, 1 h before dark onset, suppressed nocturnal elevation of N-acetylserotonin (NAS) and melatonin content and delayed the time at which the pineal melatonin content reaches a maximum by 2 h in the dark phase. It also caused a remarkable inhibition of NAT activity and failed to produce any significant changes in the content of pineal serotonin and HIOMT activity 5 h after treatment (Wakabayashi et al 1989(Wakabayashi et al , 1991a.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations